2018
DOI: 10.1002/humu.23634
|View full text |Cite
|
Sign up to set email alerts
|

ClinVar database of global familial hypercholesterolemia‐associated DNA variants

Abstract: Accurate and consistent variant classification is imperative for incorporation of rapidly developing sequencing technologies into genomic medicine for improved patient care. An essential requirement for achieving standardized and reliable variant interpretation is data sharing, facilitated by a centralized open-source database. Familial hypercholesterolemia (FH) is an exemplar of the utility of such a resource: it has a high incidence, a favorable prognosis with early intervention and treatment, and cascade sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 19 publications
2
89
0
6
Order By: Relevance
“…22 All variants were checked with Mutalyzer 2.0, as recommended by HGVS. Variants were classified as pathogenic, likely pathogenic, variant of uncertain significance (VUS), likely benign or benign, according to the American College of Medical Genetics and Genomics (ACMG) guidelines 23 following specific adaptations described in Chora et al 24 The variants reported in the present study were considered novel if they were not described before in public databases 25,26 or in PUBMED, and novel for Portugal if they were found for the first time in Portugal, but have been previously reported in another country. In silico analysis was performed as described before.…”
Section: Monogenic Dyslipidaemia Analysismentioning
confidence: 99%
“…22 All variants were checked with Mutalyzer 2.0, as recommended by HGVS. Variants were classified as pathogenic, likely pathogenic, variant of uncertain significance (VUS), likely benign or benign, according to the American College of Medical Genetics and Genomics (ACMG) guidelines 23 following specific adaptations described in Chora et al 24 The variants reported in the present study were considered novel if they were not described before in public databases 25,26 or in PUBMED, and novel for Portugal if they were found for the first time in Portugal, but have been previously reported in another country. In silico analysis was performed as described before.…”
Section: Monogenic Dyslipidaemia Analysismentioning
confidence: 99%
“…Patients with monogenic FH were defined as those with mutation(s) classified as "pathogenic" or "likely pathogenic" according to the American College of Medical Genetics and Genomics classification guidelines. 10 Weighted genetic risk scores (wGRS) for LDL-C were calculated for all patients as previously described. 11 Patients with wGRS Results: In 32 patients with monogenic heterozygous FH and 7 patients with polygenic hypercholesterolemia treated with evolocumab, absolute incremental reductions in LDL-C were 2.94 AE 1.22 mmol/L and 3.15 AE 0.90 mmol/L, respectively (P ¼ not significant), whereas percent reductions in LDL-C were 63.9% AE 16.0% and 67.7% AE 20.7%, respectively (P ¼ not significant).…”
Section: Genetic Characterizationmentioning
confidence: 99%
“…These are points that should be considered when running Exautomate on any dataset. Two other genes known to cause ~8% and ~2% of FH cases include APOB and PCSK9, encoding apolipoprotein (apo) B and proprotein convertase subtilisin/kexin type 9 (PCSK9) respectively 41 ; both genes were present on our list of significant results. Apo B is the main protein constituent of LDL particles and serves as the primary ligand for LDLR binding, allowing for the clearance of LDL particles from circulation 42 .…”
Section: Through the Development And Implementation Of Our Open-accesmentioning
confidence: 99%